"I'm F—ing Moving to Iowa:" Gender and Candidate Image in the 2020 Iowa Caucus. (March 2021) - Winfrey, Kelly L.
The 2020 presidential race started in Iowa, like it has since 1972. The slate of candidates was the most diverse ever and included six women. This study examines the relationship between candidates' gender, image, and support among Iowa voters. Iowans have access to candidates that other voters do not, so their perceptions provide unique insight into the construction of candidate images. This study examines the image qualities of leading candidates as perceived by Iowa caucus-goers in the fall of 2019. Using survey data of 576 likely Democratic caucus attendees, I examine the relationship between candidates' gender, image, and support. I find that women candidates did not benefit from stereotypical strengths of honesty and compassion, but they were perceived as strong leaders. I also find evidence of differences in image evaluations based on respondent sex, with women voters rating untraditional candidates higher than men voters.